Efficiency of sourdoughs of spontaneous fermentation from cereal flour in bakery technologies - Mykhonik, Larysa; Hetman, Inna; Naumenko, Oksana (My University, 2023)
Subject. Sourdoughs of spontaneous fermentation from buckwheat, oat and rice flour, as well as dough and bread with the addition of the above-mentioned sourdoughs. The goal is to investigate the effectiveness of the use of oat, buckwheat and rice sourdoughs of spontaneous fermentation in the technology of bread products of various assortments. Methods. When conducting research, generally accepted methods were used, as well as cause-and-effect analysis, experimental, calculation and logical generalization. Results. In the conditions of the development of discrete production and the popularity of sourdough products, it is effective to use spontaneous fermentation. At the same time, it is worth paying special attention to the search for non–traditional ingredients to improve the nutritional value of wheat flour products and dietary types of bread. The scientific novelty of the results consists in the development and description of the cycles of conducting spontaneous fermentation starters with non-traditional fermentation substrate – green buckwheat, oat and rice flour with further modeling of recipes of bread products of various assortments: wheat, wheat-rye and gluten-free. As a result of the developed management schemes, buckwheat, oat and rice sourdough of spontaneous fermentation was created and the effectiveness of their use in the technology of a wide range of bread products was proven. The feasibility of using buckwheat and oat sourdough in the recipes of wheat and wheat-rye bread, and rice and buckwheat sourdough in the recipe of gluten-free bread is justified. Using the method of trial laboratory baking, the optimal dosages of each leaven were selected and the specifics of using each of them were described, depending on the recipe of the bread. It has been established that the addition of leavens contributes to the improvement of the taste–aromatic properties of the products and more intensive acid accumulation in the dough. Scope of results. The obtained results can be used by manufacturers in the modeling of new and correction of already existing recipes of health and dietary bread.
Keywords: sourdough of spontaneous fermentation; flour of cereal crops; wheat bread; quality indicators; wheat-rye bread; gluten-free bread; кафедра технології хлібопекарських і кондитерських виробів